Hepatic cystic metastases: case report - Vargas-Alayza, César (2021)
In multiple cystic liver lesions, metastatic neoplasms should be excluded. Metastatic liver lesions are usually hypointense on T1 and hyperintense on T2 on magnetic resonance imaging, hypovascular, with septa in some xt of gastrointestinal tract neoplasia accompanied by cystic liver lesions, it is important to consider metastasis.